Competitiveness and environmental policies in strategic environmental policy models - Frank Stähler (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
This paper discusses the issue of competitiveness and environmental regulation from the viewpoint of strategic environmental policy models. It demonstrates that the incentive for strategic policies is determined only by the reaction of the opponent. Furthermore, it shows that the conditions under which relatively strict environmental policies may lead to an increase in the profits of the domestic industry are rather artificial. The result depends in a rather complex way on the type of competition and several effects of research and development or environmental quality specification, and on the assumption that a unilateral policy is possible.
Keywords: Q20; 330; Umweltpolitik; Strategische Handelspolitik; Industrielle Forschung; Technologiewahl; Spieltheorie; Internationaler Wettbewerb; Theorie